Market orientation and survival of small and medium enterprises in Nigeria - Cosmas Anayochukwu Nwankwo; MacDonald Isaac Kanyangale (Foundations of Management, 2019)
The adoption of a market orientation (MO) model for effective management of small and medium enterprises (SMEs) in Nigeria and beyond has drawn diverse views. Extant studies conducted in Nigeria in the past decades have leveraged on the existing entrepreneurial marketing model that has not significantly contributed to the survival of SMEs in Nigeria. The objective of this quantitative study is to investigate the effects of MO on the survival of manufacturing SMEs in Nigeria. The study adopted a positivistic ontology and descriptive survey design. The study randomly selected 387 owner-managers of manufacturing SMEs in Nigeria. The results show that MO significantly contributed to the survival of SMEs in Nigeria. Based on the results, the study recommends that integrative Entrepreneurial Marketing (EM) should be adopted by both the owners and managers of SMEs as this would help reduce the rate of business failure in Nigeria.
Keywords: M31; 650; market orientation; customer intensity; value creation; survival of SMEs; effects of market orientation